Microplastics in freshwater sediment: A review on methods, occurrence, and sources - Yang, Ling; Zhang, Yulan; Kang, Shichang; Wang, Zhaoqing; Wu, Chenxi (The Science of the total environment, 2021)
There is a rising concern regarding the accumulation of microplastics in the aquatic ecosystems. However, compared to the marine environment, the occurrence, transport, and diffusion of microplastics in freshwater sediment are still open questions. This paper summarizes and compares the methods used in previous studies and provides suggestions for sampling and analysis of microplastics in freshwater sediment. This paper also reviews the findings on microplastics in freshwater sediment, including abundance, morphological characteristics, polymer types, sources, and factors affecting the abundance of microplastics in freshwater sediment. The results show that microplastics are ubiquitous in the investigated sediment of rivers, lakes, and reservoirs, with an abundance of 2–5 orders of magnitude across different regions. Low microplastics concentration was observed in the Ciwalengke River with an average abundance of 30.3 ± 15.9 items/kg. In particular, an extremely high abundance of microplastics was recorded in the urban recipient in Norway reaching 12,000–200,000 items/kg. Fibers with particle size less than 1 mm are the dominant shape for microplastics in freshwater sediment. In addition, the most frequently recorded colors and types are white/transparent, and PE/PS, respectively. Finally, we conclude that the consistency of morphological characteristics and components of microplastics between the beach or marine sediments and freshwater sediments may be an indicator of these interlinkages and source-pathways. Microplastics in freshwater sediment need further research and exploration to identify its spatial and temporal variations and driving force through further field sampling and implementation of standard and uniform analytical methodologies. [Display omitted] •Microplastics occur ubiquitous in the investigated sediments of rivers, lakes and reservoirs at global scale.•The abundance of microplastics in freshwater spans 2–5 orders of magnitude across different regions.•Morphological characteristics indicate microplastics originate mainly from secondary sources.•Morphological characteristics and chemical composition of freshwater and marine sediment microplastics are consistent.